Fabrication and characterization of the copper gallium oxide thin film at different annealing temperatures - Lam, Wai Yip (2019)
The study of p-type semiconductor CuGaO2 thin film was carried out to investigate the effects of various temperatures during and after the deposition in order to obtain the optimum result in achieving a good optical transparency and conductivity of the thin film. Majority of the transparent oxide semiconductors (TOS) which were developed do not possess p-type conductivity. Due to an excess oxygen in the acceptor levels and the created holes which are firmly localized at the oxygen sites, p-type oxide semiconductors are gaining more research attention. With the increase of demand in the novel components, CuGaO2 has gained importance in research as a p-type semiconductor. Previous studies emphasized on the effects of lower temperature post-treatment of the CuGaO2 thin film of temperature lower than 500°C. The potential applications of the CuGaO2 thin films are very wide such as thinfilm transistors, transparent diodes and light-emitting diodes which are growing to be more and more relevant in the current generation. The CuGaO2 thin films were fabricated on quartz substrate via the RF magnetron sputtering technique with varying sputtering temperatures and annealing temperatures. The p-type thin films were deposited at temperatures of room temperature (RT), 50°C, 100°C, 150°C, 200°C and 250°C. Each samples of the individual deposition temperatures were also annealed at varying temperatures of 500°C, 600°C, 700°C, 800°C and 900°C. The XRD results showed that the thin films of 900°C annealing temperature has a peak approximately at 36.28° with the orientation of (012), which is based on rhombohedral unit cell with the space group R-3m (JCPDS card No. 41-0255). The crystallite size obtained is 18.040nm for the annealing temperature of 900°C while the Full-Wave Half Maximum (FWHM) value is 0.081. The optical band gaps obtained from the thin films ranged from 3.30-3.72 eV, which is in line with the results found in the general range of CuGaO2 thin film optical band gaps of 3.30-3.60 eV. From the UV-Vis measurement, the high transparencies were observed to be approximately at 70-80%. The EDS measurement of the chosen parameters of 100°C with annealing temperature of 900°C showed that the Oxide weighted at 33.75%, Copper at 27.86%and Gallium at 19.13% while the remaining 19.13% belongs to Silicon which is a part of the quartz used as the substrate. Due to the optimum surface morphology of the annealing temperature of 800°C of deposition temperature 100°C, bandgap which is within the range of general range of CuGaO2 and high transmittance are reasons suitable for diode fabrication.